Novos parâmetros para o clareamento dental: avaliação da eficácia, citotoxicidade e efeitos moleculares - Soares, Diana Gabriela de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this study, the bleaching effectiveness, cytotoxicity and phenotypic characteristic of dental pulp cells exposed to experimental in-office bleaching protocols were analyzed. In the first study, enamel/dentin discs were subjected to 6 bleaching sessions, composed by 1 or 3 applications of a 35%- or 17.5%-H2O2 (hydrogen peroxide) gel, during 5 or 15 minutes, or by a 37%-CP (carbamide peroxide) gel, applied for 10 or 20 minutes. Color change (E) and H2O2 diffusion (leucocrystal violet/ peroxidase) were analyzed. All the tested protocols promoted significant color alteration and reduction of H2O2 diffusion; however, the CP gel presented the worst results (Pillai’s trace/ Bonferroni test; p<0.05). Only the protocols 35%-H2O2/ 1x 15, 35%-H2O2/ 3x 5 min, 17.5%-H2O2/ 3x 15 min and 37%-CP 3x 20 min presented similar E values than traditional protocol (35%-H2O2/ 3x 15 min) up to 6 sessions (ANOVA; SNK and Tamhane tests/p>0.05). In the second study, the trans-enamel and trans-dentinal cytotoxicity on dental pulp cells of selected experimental bleaching protocols (35%-H2O2/ 1x 15 and 1x 5 min; 17.5%-H2O2/ 3x 15, 1x 15 and 1x 5 min) were tested. The protocol 35%-H2O2/ 3x 15 min was considered as the positive control group. The enamel/dentin discs were adapted to trans-wells devices, which were positioned over odontoblast-like cells (MDPC-23) and primary culture of human dental pulp cells (HDPCs) previously seeded on culture plates. The cell viability (MTT) and morphology (SEM) were evaluated immediately and 72 h post-bleaching, as well as oxidative stress and cell membrane damage (fluorescence microscopy). The experimental protocols promoted significant minimization of cell damage, for all evaluated parameters, when compared to positive control, in a time/concentration fashion (Kruskal-Wallis; Mann-Whitney/ p<0.05). Cells exposed to protocols with the 17.5%-H2O2 gel presented cell recovery capability in around 50% three days after bleaching...

Nesta pesquisa, foram analisadas a eficácia clareadora, citotoxicidade e características fenotípicas de células pulpares expostas a protocolos de clareamento de consultório experimentais. No primeiro estudo, discos de esmalte/dentina foram submetidos a 6 sessões clareadoras, caracterizadas por 1 ou 3 aplicações de peróxido de hidrogênio (H2O2) a 35% ou 17,5%, por 5 ou 15 min, ou de peróxido de carbamida (PC) a 37%, por 10 ou 20 min. A alteração de cor (E) e quantificação da difusão de H2O2 (violeta leuco-cristal/peroxidase) foram avaliadas. Todos os protocolos testados promoveram alteração significativa de cor associados a redução na difusão de H2O2; no entanto, o gel com PC apresentou os piores resultados (Traço de Pilai; Bonferroni/p<0,05). Apenas os protocolos 35% H2O2/ 1x 15 e 3x 5 min, 17,5% H2O2/ 3x 15 min e 37% PC/ 3x 20 min apresentaram valores de E similares ao protocolo tradicional (35%/ 3x 15 min) em até 6 sessões de clareamento (ANOVA; SNK e Tamhane/p>0.05). No segundo estudo, foi avaliada a citotoxicidade trans-amelodentinária causada pela aplicação de protocolos experimentais usando 35% H2O2/ 1x 15 e 1x 5 min e 17,5% H2O2/ 3x 15, 1x 15 e 1x 5 min. O protocolo 35% H2O2/ 3x 15 min foi empregado como controle positivo. Os discos de esmalte/dentina foram adaptados em dispositivos trans-well, os quais foram posicionados sobre células odontoblastóides (MDPC-23) e cultura primária de células pulpares humanas (HDPCs) previamente semeadas. A viabilidade (MTT) e morfologia celular (MEV) foram avaliadas imediatamente e 72 h pós-clareamento, bem como o estresse oxidativo e lesão à membrana celular (microscopia de fluorescência). Todos os protocolos experimentais avaliados reduziram significativamente o dano celular quando comparados ao controle positivo (Kruskal-Wallis; Mann-Whitney/p<0,05). Esta redução foi tempo/concentração dependente. As células expostas aos protocolos com o gel contendo 17,5% de...
Keywords: Polpa dentaria; Clareamento dental; Reabilitação bucal; Dental pulp